2009
DOI: 10.1099/vir.0.015388-0
|View full text |Cite
|
Sign up to set email alerts
|

ISG15, a ubiquitin-like interferon-stimulated gene, promotes hepatitis C virus production in vitro: implications for chronic infection and response to treatment

Abstract: Upregulation of interferon (IFN)-stimulated genes (ISGs), including IFN-stimulated gene 15 (ISG15) and other members of the ISG15 pathway, in pre-treatment liver tissue of patients chronically infected with hepatitis C virus (HCV) is associated with subsequent treatment failure (pegylated IFN-a/ribavirin). This study assessed the effect of ISG15 on HCV production in vitro. The levels of ISG15 and of its conjugation to target proteins (ISGylation) were increased by plasmid transfection, but ISGylation was inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 35 publications
4
90
0
Order By: Relevance
“…6). Similarly, ISG15 was recently reported to promote HCV replication in the HCV J6/JFH1-infected Huh-7.5 cells (47). There are several possible explanations for this difference.…”
Section: Discussionmentioning
confidence: 80%
“…6). Similarly, ISG15 was recently reported to promote HCV replication in the HCV J6/JFH1-infected Huh-7.5 cells (47). There are several possible explanations for this difference.…”
Section: Discussionmentioning
confidence: 80%
“…Previously, it was shown that the expression levels of ISG mRNA in hepatocytes or in peripheral blood are associated with the outcome of IFN-based therapy for chronic HCV infection (11,22,23). However, the predictive signature (21-probe set) did not include any ISG, indicating that baseline expression of ISG cannot predict viral relapse after successful IFN-based therapy.…”
Section: Resultsmentioning
confidence: 99%
“…ISGylated proteins are not degraded by the proteasome as ubiquitinylated proteins are (Malakhov et al 2002;Ritchie & Zhang, 2004). Recently published data indicate that ISGylation negatively modulates interferon signaling (Chua et al 2009;Broering et al 2010), in addition ISGylation and ISG15 itself directly promote HCV replication (Chen et al 2010;Broering et al 2010). These observations may explain why elevated expression of ISGs, and ISG15 in particular, during HCV infection is beneficial for the hepatitis C virus (Figure 5).…”
Section: Interferon Response; Friend or Foe?mentioning
confidence: 65%